Case report: Successful treatment of human diabetic foot ulcer using low-intensity diagnostic ultrasound combined with microbubbles: Two cases - Zhang, Xiaojuan; Cheng, Ying; Pei, Ling; Tao, Jie; Wang, Rui; Chen, Zhong (Frontiers in Endocrinology, 2022)
Background: Diabetic foot ulcer (DFU) is one of the serious complications of diabetes, which has high disability rate and mortality. Low-intensity ultrasound combined with microbubbles in blood circulation can enhance the blood perfusion effect of local soft tissue, which has the potential to promote the healing of diabetic ulcer. Here, we report how this method was used to help the healing of two patients with chronic refractory DFUs. Case Presentation: In case 1, a 56-year-old man with 3-years history of type 2 diabetes had a 3.0×2.0 cm ulcer which infected with staphylococcus aureus on his right calf for more than half a month. In case 2, a 70-year-old man with 10-years history of type 2 diabetes presented with an 8-month right heel ulcer that developed to 7.5×4.6 cm. And he also had hyperlipidemia, hypertension, and renal impairment. Both patients were enrolled in our study to receive treatment of low-intensity diagnostic ultrasound (LIDUS) combined with microbubbles. They were discharged after a 20-minute daily standard treatment for 7 consecutive days. The ulcers in both cases completely healed in 60 days and 150 days, respectively, and haven't recurred for more than one year of follow-up. Conclusion: It is feasible, safe, and effective to use commercial LIDUS combined with commercial microbubbles in the treatment of diabetic lower extremity ulcers. This study may provide an innovative and non-invasive method for the treatment of DFUs.